O acontecimento da trollagem na ordem do discurso político brasileiro: limites entre o humor e o discurso de ódio - Nascimento, Myllena Araujo do (2022)
The presence of humor in the political sphere is permeated by continuities and discontinuities related to the modes of circulation and distribution of this practice over time. Until the end of the 20th century, the archive of political discourse was more homogeneous, which means that its mode of production was more regular. Nevertheless, with the advent of the internet, this scenery changes and allows the emergence of new discursive practices, one of them being the most frequent and diverse use of humor in the political sphere, in addition to the derisive humor already found in magazines and pamphlets, for example. Currently, with the rise of the extreme right, what we find is a more expressive use of aggressive humor aimed at political opponents and social minorities. From this perspective, this dissertation aims to analyze the event of trolling in the order of Brazilian political discourse, as well as its place on the threshold between humor and hate speech. To this end, we propose to analyze the emergence, functioning and characterization of political trolling, especially after the presidential campaign from 2018 to 2021. In order to achieve this objective, we selected statements that materialize the political trolling produced by the Brazilian extreme right, observing a greater regularity of its appearance in three different materialities: political memes, public speeches and public gestures. As a theoretical-methodological contribution, we use French Discourse Analysis based on Michel Foucault's reflections, especially with regard to his archaeological method of analysis and the notions of enunciation, discontinuity and event. With this work, we demonstrate that the trolling event provoked a discursive mutation in relation to the ways of saying hate speech in political discourse, since this, in contemporary times, adapts to the use of regular humorous strategies in the digital environment.